Is forecasting with large models informative? Assessing the role of judgement in macroeconomic forecasts - Ricardo Mestre; Peter McAdam (European Central Bank (ECB), 2008)
We evaluate residual projection strategies in the context of a large-scale macro model of the euro area and smaller benchmark time-series models. The exercises attempt to measure the accuracy of model-based forecasts simulated both out-of-sample and in-sample. Both exercises incorporate alternative residual-projection methods, to assess the importance of unaccounted-for breaks in forecast accuracy and off-model judgment. Conclusions reached are that simple mechanical residual adjustments have a significant impact of forecasting accuracy irrespective of the model in use, ostensibly due to the presence of breaks in trends in the data. The testing procedure and conclusions are applicable to a wide class of models and thus of general interest.
Keywords: C52; E30; E32; E37; 330; Forecast accuracy; Forecast Projections; In-Sample; Macro-model; Out-of-Sample; Structural Break; Makroökonometrie; Zeitreihenanalyse; Vergleich; Prognoseverfahren; Stichprobenerhebung; Theorie; Schätzung; EU-Staaten